Air Temperature Sensor Estimation on Automatic Weather Station Using ARIMA and MLP - Haryas Subyantara Wicaksana; Naufal Ananda; Irvan Budiawan; Bayu Santoso; Roy Handoko; Asep Irwan Maulana; Suciarti Suciarti; Ari Utoro (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2022)
Surface meteorological quantities are now measured by Automatic Weather Station (AWS). AWS Serang records weather parameters minutely in Banten Province of Indonesia. Air temperature sensor is one instrument of this system. This study aims to design an air temperature sensor estimator model using ARIMA and Artificial Neural Network (ANN) as solution for avoiding loss data. Air temperature sensor on AWS Serang data in August of 2022 period is segmented into training, validating and testing sections. Based on criterion calculation, ARIMA (1,1,5) is simulated. It obtains not more than 0.12 of RMSE, 0.0520C of MAE, 0.193% of MAPE and 0.194% of SMAPE. Meanwhile, three different models of MLP ANN for air temperature estimator is also simulated. Input variables include air temperature, relative humidity and solar radiation intensity. Roy model has highest accuracy level for MLP ANN algorithm with 0.048 of RMSE, 0.0260C for MAE, 5% of MAPE and 4.83% of SMAPE. Overall, ARIMA (1,1,5) is better than Roy MLP ANN model in estimating air temperature sensor data on AWS Serang. Nonetheless, both models are properly fulfilling WMO (World Meteorological Organization) accuracy requirements for air temperature measurement.